Mexico : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Mexico discusses that growth is expected to accelerate modestly in the near-term, reaching 0.4 percent in 2019, as macroeconomic policies become less contractionary. Monetary policy has started easing in the context of a widening negative output gap and declining inflation. The administration's solid mandate presents an opportunity to address Mexico's longstanding structural challenges while maintaining very strong policies and policy frameworks. Staff highlighted the need to specify credible measures to reach the announced fiscal targets while adopting a more growth-friendly and inclusive policy mix. Increasing non-oil tax revenues, paired with improving the efficiency of spending, will be an imperative in this regard. The authorities have initiated a package of reforms to strengthen financial deepening and inclusion.